Simultaneous Determination Of Olmesartan And Hydrochlorothiazide In Combined Pharmaceutical Dosage Form By Rp-Hplc Method - NARENDRA DEVANABOYINA; T.SATYANARAYANA; B.GANGA RAO (International Journal of Pharma and Bio Sciences, 2012)
A simple, rapid reverse phase high-performance liquid chromatographic method was developed and validated for the simultaneous estimation of Olmesartan and Hydrochlorothiazide in bulk and pharmaceutical dosage forms. Chromatography was carried out by using Chromosil C-18,column having 250 x 4.6mm internal diameter with a mixture of methanol, acetonitrile and TEA in the ratio of 46:50:04 (v/v/v) as mobile phase. Determination of the different analytical parameters such as linearity, precision, accuracy, and specificity, limit of detection (LOD) and limit of quantification (LOQ) was done. The calibration curve was found to be linear for each analyte in the desired concentration range. The % recovery was found to be 99.59 and 99.61 for Olmesartan and Hydrochlorothiazide respectively. The proposed method is highly sensitive, precise and accurate, which was evident from the LOD value of 0.05 and 0.02 ppm for Olmesartan and Hydrochlorothiazide respectively and hence the present method can be applied successfully for the quantification of active pharmaceutical ingredient (API) content in the combined formulations of Olmesartan and Hydrochlorothiazide